Outcomes With Multidisciplinary Cardiac Rehabilitation in Post-acute Systolic Heart Failure Patients—A Retrospective Propensity Score-Matched Study - Chen, Shyh-Ming; Wang, Lin-Yi; Liaw, Mei-Yun; Wu, Ming-Kung; Wu, Po-Jui; Wei, Chin-Ling; Chen, An-Ni; Su, Tsui-Ling; Chang, Jui-Kun; Yang, Tsung-Hsun; Chen, Ching; Cheng, Cheng-I; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiac rehabilitation (CR) is recommended for patients with acute heart failure (HF). However, the results of outcome studies and meta-analyses on CR in post-acute care are varied. We aimed to assess the medium- to long-term impact of CR and ascertain the predictors of successful CR. Methods In this propensity score-matched retrospective cohort study, records of consecutive patients who survived acute HF (left ventricular ejection fraction <40) and participated in a multidisciplinary HF rehabilitation program post-discharge between May 2014 and July 2019 were reviewed. Patients in the CR group had at least one exercise session within 3 months of discharge; the others were in the non-CR group. After propensity score matching, the primary (all-cause mortality) and secondary (HF readmission and life quality assessment) outcomes were analyzed. Results Among 792 patients, 142 attended at least one session of phase II CR. After propensity score matching for covariates related to HF prognosis, 518 patients were included in the study (CR group, 137 patients). The all-cause mortality rate was 24.9% and the HF rehospitalization rate was 34.6% in the median 3.04-year follow-up. Cox proportional hazard analysis revealed that the CR group had a significant reduction in all-cause mortality compared to the non-CR group (hazard ratio [HR]: 0.490, 95% confidence interval [CI]: 0.308–0.778). A lower risk of the primary outcome with CR was observed in patients on renin-angiotensin-aldosterone system (RAAS) inhibitors, but was not seen in patients who were not prescribed this class of medications (interaction p = 0.014). Conclusions Cardiac rehabilitation participation was associated with reduced all-cause mortality after acute systolic heart failure hospital discharge. Our finding that the benefit of CR was decreased in patients not prescribed RAAS inhibitors warrants further evaluation.